Design and Development of a Heart Rate and Blood Oxygen Saturation Monitoring Device in Humans During Sleep Condition Based on the Internet of Things - Fiyanto, Roy Oktaf; Djaohar, Mochammad; Subekti, Massus; Sunawar, Aris (LPPM Universitas Negeri Jakarta, 2024)
This research aims to create a heart rate monitoring device (BPM), oxygen saturation (SpO2), and electrocardiogram (ECG) in IoT-based sleep conditions and connected to Blynk and Telegram. This tool allows monitoring BPM, SpO2, and ECG values through the LCD screen on the tool or remotely through the Blynk and Telegram applications as IoT media. This research uses engineering methods that involve designing, making tools, testing tools, data collection, and data analysis. The subjects of this research are BPM, SpO2, ECG, and the application of IoT concepts to monitor remotely and provide real-time notifications. The data analysis technique used is quantitative descriptive analysis with data collection techniques, namely laboratory observation. The conclusion of the results shows that IoT-based monitoring of heart rate and oxygen saturation in human blood has been successfully made using MAX30102 and AD8232 sensors connected to NodeMCU ESP32, as well as LCD to display measurement results. Measurements were made on twelve respondents with varying ages. The measurement was carried out by attaching the tip of the index finger of the left hand to the MAX3012 sensor to obtain BPM and SpO2 data, and attaching electrodes from the AD8232 sensor to obtain an ECG using the Bipolar lead method. The range of average heart rate measurements is at 65-94 BPM. The average value range of oxygen saturation measurements is at 95%-98%. This tool has an average measurement error value (Error) for heart rate (BPM) of 1.63% and for oxygen saturation (SpO2) of 2%. The tool also successfully connects Blynk IoT media for Realtime remote monitoring and Telegram application for remote notification media.